QTL analysis of adventitious root formation in common bean under contrasting phosphorus availability - Ochoa, Iván E.; Blair, Matthew W.; Lynch, Jonathan P. (Wiley, 2006)
Low phosphorus availability is a primary constraint to crop production in developing countries. Adventitious roots play an important role in phosphorus acquisition, as they are localized near the soil surface where phosphorus is relatively abundant. A population of recombinant inbred lines of Phaseolus vulgaris L. (G2333/G19839) was screened under high- and low-phosphorus conditions in the greenhouse and field. We observed phenotypic variation and transgressive segregation for adventitious root traits in both environments. Allometric analysis revealed that although the taproot and basal roots are closely linked to shoot growth, recombinant inbred line (RILs) differ substantially in biomass allocation for adventitious roots. A linkage map with 149 genetic markers and a total cumulative map length of 1175 cM was used to identify a total of 19 QTL across 8 of the 11 linkage groups. Together these quantitative trait loci (QTL) accounted for 19 to 61% of the total phenotypic variation for adventitious root traits in the field and 18 to 39% under greenhouse conditions. Two major QTL for adventitious rooting under low phosphorus conditions in the field were observed on linkage groups B2 and B9 that together accounted for 61% of the observed phenotypic variation. We conclude that adventitious rooting under low phosphorus is a feasible target for bean breeding.